2015
DOI: 10.3372/wi.45.45108
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the tribeAstereae(Asteraceae) in SW Asia based on nrDNA ITS and cpDNApsbA-trnHsequences

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
(29 reference statements)
1
11
0
Order By: Relevance
“…nrDNA ITS, ETS and cpDNA trnL-F have become the most frequently used molecular markers for phylogenetic studies of the tribe Astereae (Markos and Baldwin 2001, Fiz et al 2002, Li et al 2012, Jafari et al 2015, Zhang et al 2015, Xiao et al 2019. Our phylogenetic results showed that two samples of the new taxon formed a monophyletic group (ML = 100, PP = 1.00 in Fig.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…nrDNA ITS, ETS and cpDNA trnL-F have become the most frequently used molecular markers for phylogenetic studies of the tribe Astereae (Markos and Baldwin 2001, Fiz et al 2002, Li et al 2012, Jafari et al 2015, Zhang et al 2015, Xiao et al 2019. Our phylogenetic results showed that two samples of the new taxon formed a monophyletic group (ML = 100, PP = 1.00 in Fig.…”
Section: Discussionmentioning
confidence: 61%
“…However, since the 1990s its circumscription has gradually been narrowed. Mainly based on cytology evidence, Nesom (1994) denied a close taxonomical relationship between North American asters (NA asters) and Eurasian Aster (EA Aster) and excluded NA asters from Aster, a conclusion later supported by many molecular phylogenetic studies (Baldwin 1998, Noyes and Rieseberg 1999, Li et al 2012, Jafari et al 2015. Furthermore, Li et al (2012) suggested that EA Aster sensu stricto is still a polyphyletic taxon and that some Chinese species should be be segregated from Aster.…”
Section: Introductionmentioning
confidence: 99%
“…7B), Aster maackii Regel, an East Asian member of A. sect. Aster (Chen et al 2011, Jafari et al 2015) that is similar to A. tataricus L.f. (Fig. 7C), and Veratrum maackii Regel, which is also confined to East Asia (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Galasso, Bartolucci & Ardenghi, comb. nov Recent molecular studies (Li et al 2012, Jafari et al 2015 suggest the merging of the genus Tripolium Nees with Galatella Cass., although this result is not supported by anatomical and micro-morphological evidences (Karanović et al 2015). Conti et al (2005, in Italy this species is found only in Sardegna.…”
Section: F Falcinelli L Peruzzimentioning
confidence: 99%